Teachers' Efforts in Instilling Anti-Corruption Values ​​in Students: A Qualitative Study in Schools - Nayza De Joirent; Khoirun Nikmah (JUSTICES: Journal of Law, 2026)
Corruption remains a serious problem in Indonesia and requires early prevention efforts through education. Schools have a strategic role in instilling the values ​​of honesty, responsibility, and integrity in students. This study aims to describe teachers' efforts in instilling anti-corruption values ​​in students through Civics learning. The method used is descriptive qualitative, with data collection techniques through observation, interviews, and documentation. The results of the study indicate that the internalization of anti-corruption values ​​is carried out through three main steps: (1) integration of values ​​in learning, namely teachers link Civics material with issues of honesty, responsibility, and abuse of authority; (2) role models, where teachers demonstrate discipline, transparency, and honesty in assessments; and (3) habituation, through school activities that instill a culture of discipline, responsibility, and anti-cheating. These findings indicate that role models are the most dominant factor in the formation of students' anti-corruption character. This study concludes that the success of anti-corruption education is influenced by teacher consistency, school culture, and continuous habituation.